Vertical Propagation of Wave Perturbations in the Middle Atmosphere on Mars by MAVEN/IUVS. Issue 9 (21st September 2020) - Nakagawa, Hiromu; Terada, Naoki; Jain, Sonal K.; Schneider, Nicholas M.; Montmessin, Franck; Yelle, Roger V.; Jiang, Fayu; Verdier, Loic; England, Scott L.; Seki, Kanako; Fujiwara, Hitoshi; Imamura, Takeshi; et al.
Abstract: This work offers the first in‐depth study of the global characteristics of wave perturbations in temperature profiles at 20–140 km altitudes derived from the Imaging Ultraviolet Spectrograph (IUVS) onboard the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft. The peak amplitudes of waves seen in temperature profiles exceed 20% of the mean background, especially on the nightside, which is larger than those in Earth's mesosphere and thermosphere. The wave perturbations generate an instability layer around 70–100 km on the nightside, which potentially causes wave‐breaking and turbulences. Our results highlighted a seasonal variation in the latitudinal distribution of nightside perturbations. Amplitudes of wave perturbations were found to be large in the northern low‐latitude region and the southern polar region during the first half of the year ( L s = 0–180°). An increase of waves in the spectral density was found in southern low‐latitude regions in the latter half of the year ( L s = 180–360°). Vertical wavenumber spectral density in the Martian middle atmosphere shows a power‐law dependence with a logarithmic spectral slope of −3, similar to the features seen in the Earth's atmosphere. The derived spectral power density suggests the longer waves growing with height while the effective dissipation of shorter waves occurs. The strong CO2 15‐micron band cooling can effectively dissipate shorter waves. In contrast, the spectral power density at longer waves suggests an amplitude growth with height of unsaturated waves up to the lower thermosphere. Plain Language Summary: Atmospheric waves are recognized as an important part of the terrestrial climate system. This work offers the first in‐depth study of the global characteristics of wave perturbations in temperature profiles in the Martian middle atmosphere. The peak amplitudes of waves seen in temperature profiles exceed 20% of the mean background, especially on the nightside, which is larger than those in Earth's mesosphere and thermosphere. We find that the wave perturbations generate an instability layer around 70–100 km on the nightside. The longer waves suggest the amplitudes grow with height which becomes large enough to distort the Martian upper atmosphere significantly. Key Points: MAVEN/IUVS revealed for the first time the global characteristics of wave perturbations in temperature profiles from 20 to 140 km altitude The peak amplitudes of waves exceed 20% of the mean background values on the nightside, larger than those in Earth's mesosphere Amplitudes appear to grow with height for longer wavelengths, whereas dissipation of shorter wavelengths occur